Seismic Response Analysis of Fully Base-Isolated Adjacent Buildings with Segregated Foundations - Khaled Ghaedi; Zainah Ibrahim; Mohammed Jameel; Ahad Javanmardi; Hamed Khatibi (Advances in Civil Engineering)
In populous cities, construction of multistorey buildings close to each other due to space limitation and increased land cost is a dire need. Such construction methods arise several problems during earthquake excitation. The aim of this study is to investigate the bidirectional seismic responses of fully base-isolated (FBI) adjacent buildings having different heights and segregated foundations. Therefore, two scenarios, namely, (a) investigation of the responses of FBI adjacent buildings compared to those with fixed base (FFB) and (b) the effects of separation distance on FBI adjacent buildings, were studied. Based on these investigations, the results showed that isolation system significantly enhances the overall responses of the BI buildings. Spectacularly, the base isolation system was further efficient to decrease displacement rather than the acceleration. In addition, increase of the seismic gap changed the acceleration, pounding, base shear, base moment, and storey drift, as well as the force-deformation performance of the isolators. Therefore, it seems a need to focus on the effect of the separation distances for the design of base isolators for FBI adjacent buildings in future works.